Hepatoprotective effect of Monotheca buxifolia fruit against antitubercular drugs-induced hepatotoxicity in rats (Bangladesh Journal of Pharmacology, 2016)
The present study investigates the hepatoprotective potential of Monotheca buxifolia fruit hydro-ethanolic extract, against isoniazid- and rifampicin- induced hepatotoxicity in rats. Phytochemical investigations lead to the isolation of oleanolic acid and isoquercetin. Pretreatment with M. buxifolia extract at doses of 150 and 300 mg/kg for 21 days, restored the isoniazid- and rifampicin-induced elevation of serum levels of alanine aminotransferase (p